2016
DOI: 10.14238/sp17.3.2015.180-4
|View full text |Cite
|
Sign up to set email alerts
|

Pertambahan Berat Badan Pasca Penutupan Patent Duktus Arteriosus secara Transkateter

Abstract: Latar belakang. Patent duktus arteriosus (PDA) merupakan salah satu penyakit jantung bawaan asianotik yang paling banyakdijumpai pada anak. PDA dapat memengaruhi pertumbuhan anak dan menyebabkan malnutrisi pada anak dan malnutrisi yangterjadi merupakan faktor risiko mortalitas dan morbiditas pada anak.Tujuan. Mengetahui pertambahan berat badan sebelum dan sesudah dilakukan tindakan penutupan duktus pada anak dengan PDAsecara transkateter dan untuk mengetahui faktor-faktor yang berpengaruh terhadap pertambahan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…34 In Yogyakarta, malnutrition was noted in 76.7% of patients diagnosed with PDA. 14 Similarly, 80% of our patients had malnutrition, including 40% with severe malnutrition prior to transcatheterization. An Egyptian study concluded that malnutrition in PDA patient significantly correlated with low hemoglobin level, low oxygen saturation, pulmonary hypertension, heart failure, and history of poor nutritional intake.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…34 In Yogyakarta, malnutrition was noted in 76.7% of patients diagnosed with PDA. 14 Similarly, 80% of our patients had malnutrition, including 40% with severe malnutrition prior to transcatheterization. An Egyptian study concluded that malnutrition in PDA patient significantly correlated with low hemoglobin level, low oxygen saturation, pulmonary hypertension, heart failure, and history of poor nutritional intake.…”
Section: Resultsmentioning
confidence: 53%
“…8,29,30 In addition to monitoring for complications, some studies also assessed changes in LVF parameters and body weight, but most monitoring was not done for a full year after closure. 11,14,31,32 We monitored both LVF parameters and nutritional status, according to the WHO or CDC growth charts depending on patient age. 15 A Nigeria study reported that 92% of CHD patients had malnutrition and 90% of those had severe malnutrition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations